Strong exciton-photon coupling in large area MoSe2 and WSe2 heterostructures fabricated from two-dimensional materials grown by chemical vapor deposition. (18th November 2020) - Gillard, Daniel J; Genco, Armando; Ahn, Seongjoon; Lyons, Thomas P; Yeol Ma, Kyung; Jang, A-Rang; Severs Millard, Toby; Trichet, Aurélien A P; Jayaprakash, Rahul; Georgiou, Kyriacos; Lidzey, David G; Smith, Jason M; et al.
Abstract: Two-dimensional semiconducting transition metal dichalcogenides embedded in optical microcavities in the strong exciton-photon coupling regime may lead to promising applications in spin and valley addressable polaritonic logic gates and circuits. One significant obstacle for their realization is the inherent lack of scalability associated with the mechanical exfoliation commonly used for fabrication of two-dimensional materials and their heterostructures. Chemical vapor deposition offers an alternative scalable fabrication method for both monolayer semiconductors and other two-dimensional materials, such as hexagonal boron nitride. Observation of the strong light-matter coupling in chemical vapor grown transition metal dichalcogenides has been demonstrated so far in a handful of experiments with monolayer molybdenum disulfide and tungsten disulfide. Here we instead demonstrate the strong exciton-photon coupling in microcavities composed of large area transition metal dichalcogenide/hexagonal boron nitride heterostructures made from chemical vapor deposition grown molybdenum diselenide and tungsten diselenide encapsulated on one or both sides in continuous few-layer boron nitride films also grown by chemical vapor deposition. These transition metal dichalcogenide/hexagonal boron nitride heterostructures show high optical quality comparable with mechanically exfoliated samples, allowing operation in the strong coupling regime in a wide range of temperatures down to 4 Kelvin in tunable and monolithic microcavities, and demonstrating the possibility to successfully develop large area transition metal dichalcogenide based polariton devices.